Strategies to Increase the Tourism Attractiveness of Lombok Timur, Indonesia through Smart City - M Khalilurrahman Ali Akbar; Firmansyah, Firmansyah; Orchidamoty, Orchidamoty (English and Tourism Studies, 2023)
This research aims to find out how the strategy of increasing tourist attraction in Lombok Timur Regency through smart city and how the obstacles experienced when implementing smart city in Lombok Timur Regency. By using a descriptive qualitative approach. And by using primary data and secondary data. Data collection using interview, observation and documentation methods. The results of this study indicate that the strategy carried out in increasing tourist attractiveness in Lombok Timur through smart city takes time so that its implementation can run optimally. Some of the strategies carried out by the local government are by making the Lotim Go application, Social Media Branding, the Pesona Gumi Selaparang Programme, and the Tourism Website. The above strategies are made as a form of effort to make it easier for tourists to obtain tourist information in Lombok Timur. And by implementing this strategy, it is hoped that it can make tourist destinations continue to grow and develop, can increase the number of tourist visits and increase local revenue (PAD). The obstacles in implementing and innovating smart cities in Lombok Timur Regency experienced by the local government are position transfers, budget constraints, lack of socialisation, lack of coordination between regional apparatus organisations and lack of IT experts.